Characterization of physicochemical and antimicrobial properties of plasma‐treated starch/chitosan composite film. Issue 7 (22nd April 2021) - Sheikhi, Zhian; Mirmoghtadaie, Leila; Abdolmaleki, Khadije; Khani, Mohammad Reza; Farhoodi, Mehdi; Moradi, Ehsan; Shokri, Babak; Shojaee‐Aliabadi, Saeedeh
Abstract: The aim of this study was to examine mechanical and physical properties of starch/chitosan composite film exposed to low‐pressure air and argon plasma at 600 mTorr for different duration (4, 8 and 12 min) and evaluate the shelf life of the chicken breast fillet packaged with plasma‐treated films. The mechanical properties of the composite films were improved significantly. It is shown that argon plasma is more efficient in improving the tensile strength of the films and increased it from 10.59 to 22.09 Mpa after 12 min of process due to the formation of a stable cross‐linked network on the surface of the polymer, although film's stretchability, modified in air plasma, was significantly more. Solubility and hydrophilicity of the films were increased; however, no significant change in the water vapor transmission rate was observed. Oxygen permeability of films improved after both plasma treatment. Total viable count and oxidative (TBA) changes of fillets were analyzed during shelf life. The results showed that Cold plasma treatment could not prolong the shelf life of the fillets through plasma‐treated films. Abstract : Plasma treated chitosan/starch film was used for packaging of chicken breast fillet.